Diamond‐based Magnetic Microscopy: Quantum Magnetic Imaging of Iron Biomineralization in Teeth of the Chiton Acanthopleura hirtosa (Small Methods 3/2020). Issue 3 (6th March 2020) - McCoey, Julia M.; Matsuoka, Mirai; de Gille, Robert W.; Hall, Liam T.; Shaw, Jeremy A.; Tetienne, Jean‐Philippe; Kisailus, David; Hollenberg, Lloyd C. L.; Simpson, David A.
Abstract : Chitons are marine molluscs that mineralize iron to form hard, abrasion‐resistant teeth. In article number 1900754 Julia M. McCoey, David A. Simpson, and co‐workers, describe how diamond‐based magnetic microscopy can be applied to study the magnetic properties of chiton teeth. The imaging methods reveal highly ordered magnetic domains at the micron scale, providing new insight into the assembly of these exquisite materials.